Sistem Rekrutmen Guru terhadap Mutu Lembaga Pendidikan di MTs. Ma’arif 16 Nurul Hidayah Banyubang Solokuro Lamongan - M Zahid Zaman; Waslah Waslah; Emi Lilawati (Universitas KH. A. Wahab Hasbullah, 2022)
This research aims to describe and analyze the teacher recruitment system in MTs. Ma'arif 16 Nurul Hidayah Banyubang Solokuro Lamongan, and improve the quality of educational institutions through the teacher recruitment system. This research uses a qualitative approach. Research data is obtained through observation and interview methods. Data obtained in the analysis by means of data reduction, presentation of data, and withdrawal of conclusions. The results of research conducted in the field showed that the teacher recruitment system in MTs. Ma'arif 16 Nurul Hidayah is that there are stages determined by the school.